A defined co‐culture of Geobacter sulfurreducens and Escherichia coli in a membrane‐less microbial fuel cell. Issue 4 (22nd November 2013) - Bourdakos, Nicholas; Marsili, Enrico; Mahadevan, Radhakrishnan
ABSTRACT Wastewater‐fed microbial fuel cells (MFCs) are a promising technology to treat low‐organic carbon wastewater and recover part of the chemical energy in wastewater as electrical power. However, the interactions between electrochemically active and fermentative microorganisms cannot be easily studied in wastewater‐fed MFCs because of their complex microbial communities. Defined co‐culture MFCs provide a detailed understanding of such interactions. In this study, we characterize the extracellular metabolites in laboratory‐scale membrane‐less MFCs inoculated with Geobacter sulfurreducens and Escherichia coli co‐culture and compare them with pure culture MFCs. G. sulfurreducens MFCs are sparged to maintain anaerobic conditions, while co‐culture MFCs rely on E. coli for oxygen removal. G. sulfurreducens MFCs have a power output of 128 mW m−2, compared to 63 mW m−2 from the co‐culture MFCs. Analysis of metabolites shows that succinate production in co‐culture MFCs decreases current production by G. sulfurreducens and that the removal of succinate is responsible for the increased current density in the late co‐culture MFCs. Interestingly, pH adjustment is not required for co‐culture MFCs but a base addition is necessary for E. coli MFCs and cultures in vials. Our results show that defined co‐culture MFCs provide clear insights into metabolic interactions among bacteria while maintaining a low operational complexity. Biotechnol. Bioeng. 2014;111: 709–718. © 2013 Wiley Periodicals, Inc.